THE EFFECT OF EMOTIONAL INTELLIGENCE ON JOB BURNOUT WITH EMPLOYEE ENGAGEMENT AS THE MEDIATOR ON MILLENNIALS AND GENERATION Z IN INDONESIA - Layla Safira, Haydee
The workforce is started to be dominated by millennial and gen Z employees. Millennial employees would be characterized as the ones that would show confidence with a strong desire for work, meanwhile, gen Z would be considered as the ones who are intrigued by organizations that make a social impact. However, it is found that millennial & gen Z employees are experiencing job burnout from their work. Hence, this research is proposed to see (1) the effect of emotional intelligence on job burnout (2) the effect of emotional intelligence on employee engagement (3) the effect of emotional intelligence on job burnout mediated by employee engagement. The research uses a quantitative method with a sample of 224 respondents consisting of millennial and gen Z employees. The data will be obtained using an online questionnaire, processed using IBM SPSS Statistics, and analyzed using path analysis. The research found that there is no significant effect of emotional intelligence on job burnout (Sig = .153 > 0.05). There is also no significant effect on job burnout mediated by employee engagement (the indirect effect is smaller than the direct effect = 0.036 > 0.066). However, through this study, it is found that there is a positive significant effect of emotional intelligence on employee engagement (Sig = <.001 smaller than 0.05). Thus, the research came to the conclusion that employees with high emotional intelligence will be more likely to be engaged in the workplace.